Respon Struktur Bangunan Rumah Sakit Terhadap Gempa dengan Struktur Beton Bertulang ddan Baja - Pradana , Muhammad Caesar; Rabbani, Nauval (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
In Indonesia, particularly in regions such as Java Island, natural disasters like earthquakes occur frequently. Therefore, it is crucial to construct earthquake-resistant buildings with life safety performance. This means that although buildings may suffer damage, they should not collapse completely, allowing sufficient time for evacuation. In many projects in Indonesia, reinforced concrete structures and steel structures are commonly used. The aim of this study is to determine the differences in base shear forces and displacements between reinforced concrete structures and steel structures when subjected to seismic forces. To conduct this research, the author utilized data processing methods from structural modeling results using SAP2000 V14 software. The modeling results show that reinforced concrete structures have higher base shear forces than steel structures but have lower displacements. These values are directly influenced by the inherent properties of each structure. Reinforced concrete structures have greater weight and stiffness compared to steel structures, while steel structures are lighter in weight and more flexible.